CHARACTERISATION OF ALKALINE LIPASE FROM AN ARCTIC YEAST STRAIN RHODOSPORIDIUM BABJEVAE BD19 - lukaszewicz, Marcin; Jablonski, Slawomir; Krasowska, Anna (European Scientific Journal, ESJ, 2013)
The yeast strain isolated from freshwater from Arctic Archipelago of Svalbard was identified biochemically by API C 20 aux test, genetically by 18S rRNA and ITS sequencing as Rhodosporidium babjevae BD19. R. babjevae secreted into the culture medium lipase with the activity 67.7 U/ml after 144 hours of growth on Tween 80 as a sole of carbon source and 115.5 U/ml after 144 hours on inorganic ammonium sulphate as a sole nitrogen source. The molecular mass of purified lipase was 37.6 kDa and optimum esterasic activity was at pH 9.0 and 30 oC. The chain length specificity of the enzyme was determined using p-nitrophenyl fatty acids esters as substrates and the highest hydrolysis rate was with p-nitrophenyl caprylate. The R. babjevae BD19 lipase seems to have unique 1-position specificity when hydrolyzing triolein.